Implementation of Interactive Learning Media Based on Virtual Laboratory on Student Science Literacy Skills - Polihito, Nurhalima; Abdjul, Tirtawaty; Ntobuo, Nova Elysia; Yusuf, Muhammad; Odja, Abdul Haris; Nurhayati, Nurhayati (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Virtual laboratories allow students to simulate experiments/practical work. This study aims to describe the application of interactive learning media based on virtual laboratories on students' scientific literacy skills in the material of substances and changes. This study uses a one-group pretest-posttest design, with three classes as research samples. The study was conducted in two schools, namely SMP Negeri 1 Tilango and SMP Negeri 1 Tilongkabila. The results of the study showed a significant increase in students' scientific literacy skills after students participated in learning using virtual laboratory media based on PhET Simulation. This media provides students with the opportunity to conduct virtual experiments, which has an impact on increasing their understanding of concepts and critical thinking skills. Based on the results of the analysis, the average posttest score of students was higher than the pretest score, which was 89.35 in the experimental class, 91.90 in replication class 1, and 88.64 in replication class 2. This fact shows that the use of virtual laboratories plays a positive role in improving student learning achievement. Thus, interactive learning media based on virtual laboratories can be used as an effective alternative to support science learning at the junior high school level.